F@ce: a team-based, person-centred intervention for rehabilitation after stroke supported by information and communication technology – a feasibility study - Susanne Guidetti; Martha Gustavsson; Kerstin Tham; Magnus Andersson; Uno Fors; Charlotte Ytterberg (BMC Neurology, 2020)
Abstract Background Globally, there is a growing use of Information and Communication Technology (ICT), including mobile phones, tablets and computers, which are being integrated into people’s daily activities. An ICT-based intervention called F@ce was developed in order to provide a structure for the process in stroke rehabilitation and facilitate change by integrating a global problem-solving strategy using SMS alerts. The aim of the study was to evaluate the feasibility of i) F@ce within in-patient and primary care rehabilitation after stroke, ii) the study design and outcome measures used, and iii) the fidelity, adherence and acceptability of the intervention. Methods Three teams comprising occupational therapists and physiotherapists who work in neurological rehabilitation participated in a preparatory workshop on F@ce and then enrolled 10 persons with stroke to participate in the intervention. Goals were set using the Canadian Occupational Performance Measure (COPM) and the participants with stroke rated their performance and satisfaction with the activities associated with the three goals every day for 8 weeks. Data were collected at inclusion, at four and 8 weeks, using the COPM, Stroke Impact Scale, Frenchay Activities Index, Life Satisfaction Checklist, Self-Efficacy Scale, Hospital Anxiety and Depression Scale, Fatigue Severity Scale, follow-up survey, daily ratings on the web platform and logbooks. Results All of the participants showed increased scores in the primary outcome (COPM) and a clinically meaningful improvement of ≥2 points was found in four participants regarding performance and in six participants regarding satisfaction. Overall fidelity to the components of F@ce was good. The response rates to the F@ce web platform were 44–100% (mean 78%). All of the participants stated that F@ce had supported their rehabilitation. Conclusion The results indicate that the most beneficial part of F@ce was the person-centred, goal-setting process and SMS alerts. All participants were satisfied with F@ce and highlighted the benefits of receiving daily alerts about their goals. This encouraged them to be more active. The only downside mentioned was that they felt under an obligation to practice, although this was described as “a positive obligation”.